Protectiveness of Artesunate Given Prior Ischemic Cerebral Infarction Is Mediated by Increased Autophagy - Shao, Ming; Shen, Yue; Sun, Hongjing; Meng, Delong; Huo, Wei; Qi, Xu (Frontiers in Neurology, 2018)
Background: Ischemic cerebral infarction is a severe clinical condition that can cause serious mortality. Artesunate, an anti-malarial drug that is widely used in cancer treatment, is known to facilitate accelerated cell apoptosis. The aim of this study is to explore the possible neuroprotective effects of artesunate on hypoxic-ischemic cells in rats. Methods: Middle cerebral artery occlusion (MCAO) rats were treated with artesunate in different doses to observe their survival rate. Primary hippocampal neurons were deprived of oxygen-glucose to induce ischemia symptoms. Western blot was performed to determine the protein expressions of p-mTOR, Beclin-1, and Mcl-1. A five-point scale was used to detect neurological deficit. Cell apoptosis was measured using a TUNEL assay. Results: Artesunate supplementation protected MCAO rats from death and ameliorated brain injury among them. Artesunate administration decreased the expression of p-mTOR, increased the expressions of Beclin-1 and Mcl-1, and decreased the activity of caspase-3 in both the rats' ischemia cerebral cortices and their primary ischemia hippocampal neurons when compared with artesunate-absent ischemic brains and cells. The neuroprotective effects of artesunate were abolished by either leucine (LEU) or 3-MA, while the effects of rapamycin were reversed by 3-MA. In vivo experiments verified the protective effects of artesunate on brain-infarct rats. Conclusion: The results indicate the protectiveness of artesunate against ischemic cerebral infarction, whereas the protectiveness might increase autophagy through regulating the activity of mTOR.